Consumer Trust in E-Commerce Platforms: The Role of Digital Marketing Strategies and Perceived Data Security - Syarkani, Yofy (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
Consumer trust serves as a critical determinant of success for e-commerce platforms in the digital economy. This study aims to explore how digital marketing strategies and perceived data security contribute to the formation and enhancement of consumer trust. Using a structured literature review approach, relevant peer-reviewed journal articles were systematically identified and synthesized to extract thematic insights. The findings reveal that personalized marketing, transparency in communication, and influencer endorsements significantly impact trust-building. Additionally, consumers' perception of robust data protection mechanisms strongly influences their willingness to engage in online transactions. The interplay between marketing efforts and perceived security creates a comprehensive trust environment that fosters long-term customer relationships. The study also highlights the role of brand credibility, user experience design, and regulatory compliance in reinforcing consumer confidence. By integrating theoretical perspectives from trust theory and information systems, this review provides a nuanced understanding of trust formation in e-commerce. The results offer valuable implications for practitioners aiming to improve consumer engagement and loyalty. Future research is recommended to examine trust dynamics in emerging markets and under-represented consumer segments.